Correction of lying ear and aesthetic modification of helix and ear lobule with hyaluronic acid filler injection: Experience in Chinese patients - Yiming Li; Weiwei Dong; Lingmei Zhang; Ying Yang; Yang Song; Ning Shi; Shiyi Li; Mohd Firdaus Mohd Hayati; Ling, Sophia Heng Si; Yujun Tang (Oxford University Press, 2024)
Background: Large and long ears are regarded as symbols of wealth and health in East Asian culture, and people with lying ears often want their ears to be more exposed and prominent. Surgeries to correct lying ears have been documented. Objectives: The aim of this study was to report the correction of lying ears and the aesthetic modification of helix and ear lobule with hyaluronic acid (HA) injections. Methods: HA injections were performed at the auriculocephalic sulcus to increase the cranioauricular angle (CA) and correct lying ears. The injections at helix and lobule were case specific. The CA was measured and photographs were taken at baseline and at 1-, 3-, 6-, and 10-month follow-ups. Efficacy was assessed with the 5-point Global Aesthetic Improvement Scale (GAIS). Adverse events were recorded. Results: Forty-six patients (92 ears) received HA injections and completed follow-ups. Instant correction outcomes were observed. Sixteen (34.8%) patients received 1 touch-up injection, the clinical efficacy of which persisted for 1 to 1.5 years. For over 90% of cases with touch-up treatment the GAIS was “very much improved” or “much improved” at all follow-ups. The GAIS for over 70% of cases without touch-up treatment was “very much improved” or “much improved” at 1-, 3-, and 6-month follow-ups. CA increased significantly compared with the baseline. Patients also reported “more V-shaped face shape” and “lifted jawline” effects. No serious adverse events occurred. Conclusions: As an alternative technique to surgeries, HA filler injections at the auriculocephalic sulcus effectively corrected lying ears. This technique produced immediate, long-lasting, and aesthetically pleasing results. The side effects and downtime were minimal